Koping Individu Berhubungan dengan Kepatuhan Berobat Penderita Tuberkulosis Paru di Kabupaten Konawe - Atoy, Lena; Syukur Bau, Abd (Health Information : Jurnal Penelitian, 2021)
The incidence of pulmonary tuberculosis (pulmonary TB) is still high in Southeast Sulawesi Province. Mycobacterium tuberculosis can only be treated by following a long course of treatment. This study aimed to determine the relationship between individual coping with treatment adherence of pulmonary TB patients in Konawe district. Total sampling method was used in determining the sample size, and data collection using observation sheets. A total of 60 respondents participated in this study. The results of the Chi-square statistical test with a p value of 0.001, there was a relationship between individual coping with treatment adherence of pulmonary TB patients.